Identity, household work, and subjective well-being among rural women in Bangladesh - Seymour, Gregory; Floro, Maria S. (International Food Policy Research Institute, 2016)
Despite increases in women’s employment, significant gender disparity exists in the time men and women spend on household and care work. Understanding how social expectations govern gender roles and contribute to this disparity is essential for designing policies that effectively promote a more equitable household division of labor. In this study, we examine how a woman’s identity may affect the trade-offs between the time she spends on household and care work and her well-being, using an analytical framework we develop based on the work of Akerlof and Kranton. Analyzing data from rural Bangladesh, we find that longer hours spent on household work are associated with lower levels of subjective well-being among women who disagree with patriarchal notions of gender roles, while the opposite is true for women who agree with patriarchal notions of gender roles. Importantly, this pattern holds only when a woman strongly identifies with patriarchal or egalitarian notions of gender role.